A Comprehensive Exploration of Lecturer’s Written Corrective Feedback on Students’ Counterargument Paragraphs in Enhancing Argumentative Writing Proficiency - Himma Jihadiah Arrosyidah; Ahmad Munir; Ali Mustofa (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: This study delved into the methods employed by lecturers when offering feedback on argumentative essays authored by students. It particularly emphasized examining the feedback mechanism about counterargument paragraphs within these essays. Method: The research utilized a qualitative method to delve into the feedback provided by the lecturer on students' argumentative essays. This involved thoroughly exploring the various types of feedback imparted by the lecturer. Additionally, document analysis served as the primary means of data collection, enabling a comprehensive examination of written feedback and its nuance. Results: The results emphasize the importance of feedback in improving writing skills and suggest that lecturers should continue to give clear and direct feedback. Novelty: In the context of existing literature on lecturer's written corrective feedback, this study provides valuable insights into students' argumentative writing dynamics. It highlights the significance of using clear feedback to enhance writing skills, benefiting lecturers and students in academic writing. Additionally, feedback on counterarguments could increase writing proficiency since it is usually the weakest point.